Colonization of the streptomycin-treated mouse large intestine by a human fecal Escherichia coli strain: role of growth in mucus. - Wadolkowski, E A (1988)
The relative colonizing abilities of Escherichia coli F-18, isolated from the feces of a healthy human, and E. coli F-18col-, a strain derived from it which does not make the E. coli F-18 colicin, were studied. In a previous report, it was shown that when each strain was fed individually to streptomycin-treated mice, at approximately 10(10) CFU per mouse, each colonized the large intestine at between 10(7) and 10(8) CFU/g of feces indefinitely. However, when simultaneously fed to mice, although E. coli F-18 colonized at about 10(8) CFU/g of feces, E. coli F-18col- dropped to a level of 10(3) CFU/g of feces within 3 to 5 days. In the present investigation, we show that when given enough time to establish a state of colonization, E. coli F-18col- persists in feces in high numbers despite subsequent challenge by E. coli F-18. Therefore, a major defect in the ability of E. coli F-18col- to colonize in the presence of E. coli F-18 appears to be in initiating that state. In addition, when mucus was scraped from the cecal wall and, without further treatment, was inoculated with E. coli F-18 or F-18col-, both strains grew well. However, when cecal mucus was inoculated with both strains simultaneously, E. coli F-18 grew far more rapidly than E. coli F-18col-. Moreover, neither strain grew in cecal luminal contents. Together, these data suggest the possibility that both E. coli F-18 and F-18col- must grow in mucus to colonize the streptomycin-treated mouse large intestine, that E. coli F-18col- is eliminated by E. coli F-18 because it does not grow in mucus as well as E. coli F-18, and that E. coli F-18col- can resist elimination by E. coli F-18 if it is allowed enough time to establish itself within the mucus layer.